Impact of Dynamic Non-Equilibrium Processes on Fracture Mechanisms of High-Strength Titanium Alloy VT23; Metals; Vol. 8, iss. 12 - Marushchak P. O. Pavel Orestovich; Konovalenko I. Igor; Chausov M.; Pylypenko A. P. Andriy Petrovich; Panin S. V. Sergey Viktorovich; Vlasov I. V. Iljya Viktorovich; Prentkovskis O. Olegas (2018, 2018)
Title screen